Improvement of Step Tracking Algorithm Used for Mobile Receiver System via Satellite - Tran Van Hoi; Nguyen Xuan Truong; Bach Gia Duong (Institute of Advanced Engineering and Science, 2015)
In the mobile communication via satellite, received systems are mounted on the mobile device such as ship, train, car or airplane. In order to receive continuous signals, received antenna system must be steered in both the azimuthal and elevation angle to track a satellite. This paper proposes the improved step-tracking algorithm using for mobile receiver system via satellite Vinasat I. This paper also presents the results of study, design and manufacture of the discrete-time controller system for the fast tracking of a satellite by applying an improved step tracking algorithm with fuzzy proportional integral derivative proportional integral derivative controller. Simulated and experimental results indicate that the system performances obtain from applying the improved step tracking algorithm and the fuzzy controller was better than traditional control systems.